Translational Significance for Tumor Metastasis of Tumor-Associated Macrophages and Epithelial–Mesenchymal Transition - Song, Wenzhe; Mazzieri, Roberta; Yang, Tao; Gobe, Glenda C. (Frontiers in Immunology, 2017)
The tumor microenvironment determines development and progression of many cancers. Epithelial-mesenchymal transition (EMT) is fundamental to tumor progression and metastasis not only by increasing invasiveness, but also by increasing resistance to cell death, senescence and various cancer therapies, determining inflammation and immune surveillance, and confering stem cell properties. It does this by enabling polarized epithelial cells to transform into cells with a mesenchymal, and therefore motile, phenotype. Tumor-associated macrophages (TAMs) are key cells of the tumor microenvironment that orchestrate the connection between inflammation and cancer. Activation of EMT often requires crosstalk between cancer cells and components of the local tumor microenvironment, including TAMs. In this review, clinical and experimental evidence is presented for control of TAMs in promoting cancer cell invasion and migration, and their interaction with the EMT process in the metastatic cascade. The translational significance of these findings is that the signaling pathways that interconnect TAMs and EMT-modified cancer cells may represent promising therapeutic targets for the treatment of tumor metastasis.